PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG DAN PERPUTARAN TOTAL AET TERHADAP RETURN ON ASSET PADA PERUSAHAAN GARMEN DAN TEKSTIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Adi Dwi Purnomo; Hanifah Hanifah; Reza Mukhlisin (Universitas La Tansa Mashiro, 2016)
Profitability is one of the ways used to assess the extent to which a company's ability to capitalize on the normal activities of the business is the management of raw materials into finished goods ready for sale and profit from the sales proceeds. The level of return on asset can be affected by many factors, one satunnya is inventory turnover, accounts receivable turnover, and total asset turnover. Penellitian aims to study the effect of inventory turnover, accounts receivable turnover, and total asset turnover on return on asset in garment and textile companies listed on the Indonesia Stock Exchange. The population of this research is all garment and textile companies listed on the Indonesia Stock Exchange in 2012-2015. Samples were taken by using purposive sampling method in order to obtain the 14 companies that qualify for the research sample. This study uses regression analysis to determine the effect of independent variables consisting of inventory turnover, accounts receivable turnover, and total asset turnover. From the results of data analysis using SPSS (Statistical Package For Social Science) version 20.0. Found regression equation Y '= 1.474 - 0,135X1 - 8,384X3 + 0,926X2 + e, results of this study indicate that the inventory turnover does not affect the return on asset evidenced by nillai greater significance than 0,782 alpha > 0.05. Accounts receivable turnover significantly influence return on asset with significant value 0.000 < 0.05. Total asset turnover significant positive effect on return on asset with significant value 0.001 < 0.05. Simultaneously variable inventory turnover, accounts receivable turnover, and total asset turnover affect the return on assets.